2021
DOI: 10.2217/cns-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and outcomes for patients with newly diagnosed glioblastoma multiforme: a retrospective cohort study

Abstract: Aim: Investigate real-world outcomes and healthcare utilization of patients with glioblastoma multiforme (GBM) related to O6-methylguanine DNA methyltransferase (MGMT) promoter testing and methylation. Patients & methods: US Oncology Network data were analyzed for patients receiving first-line (1L) treatment for GBM. Results: Most patients received 1L radiation with temozolomide. Unadjusted median overall survival (OS) was higher in tested versus untested (median:18.1 vs 11.8 months) and in methylated vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, we note that all patients included in the Girvan cohort received at least two LOTs, whereas only 67.1% of patients in our cohort received 2L therapy. Another cohort of 750 patients with GBM assembled by Annavarapu et al 23 showed that the majority of patients received 1L radiation concurrent with temozolomide (90.1%), bevacizumab was the most common 2L therapy (73.4% of patients receiving 2L therapy), and the median 1L duration was 135.1 days. That study defined treatment duration as the interval between the date of LOT initiation and the date of last administration, which does not account for the date of initiation for the subsequent LOT.…”
Section: Discussionmentioning
confidence: 99%
“…However, we note that all patients included in the Girvan cohort received at least two LOTs, whereas only 67.1% of patients in our cohort received 2L therapy. Another cohort of 750 patients with GBM assembled by Annavarapu et al 23 showed that the majority of patients received 1L radiation concurrent with temozolomide (90.1%), bevacizumab was the most common 2L therapy (73.4% of patients receiving 2L therapy), and the median 1L duration was 135.1 days. That study defined treatment duration as the interval between the date of LOT initiation and the date of last administration, which does not account for the date of initiation for the subsequent LOT.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, promoter methylation of the MGMT gene is associated with a favourable prognosis and a better response to TMZ treatment [32]. Several studies confirmed this association and reported a higher overall survival and better response to treatment compared to patients without methylation of the MGMT gene [61][62][63][64][65]. For patients in this situation, O 6 -benzylguanine (O 6 -BG) can be used for MGMT inactivation.…”
Section: Mgmt Promoter Methylationmentioning
confidence: 99%
“…MGMT, a cellular DNA repair enzyme that neutralizes the cytotoxic effects of alkylating drugs like TMZ, is another important biological component related to clinical response in GB patients ( 165 ). It has been demonstrated that MGMT promoter methylation is a mechanism of MGMT regulation in gliomas, which is a favorable predictor of progression-free survival and overall survival in TMZ-treated patients ( 166 ). In this respect, Weathers et al.…”
Section: Cmv-specific Adoptive T Cell Therapymentioning
confidence: 99%